Conflict Management Strategies as Moderators of Burnout in the Context of Emotional Labor - Anabela Rodrigues; Micaela Francisco; Íris M. Oliveira; Ângela Leite; Sílvia Lopes (Societies)
This study explores the relationship between emotional labor and burnout, focusing on the moderating role of conflict management strategies. A total of 233 employees from diverse sectors in Portugal participated in this cross-sectional investigation. We employed the Emotional Labor Scale (ELS) and the Oldenburg Burnout Inventory (OLBI) to quantitatively assess emotional labor and burnout levels. Additionally, the study examined conflict management practices in the workplace using the Conflict Management Strategies Assessment Scale (ROCI-2). The findings reveal that participants reported high emotional labor and burnout levels and a positive correlation between these constructs. As expected, conflict management strategies were found to moderate this relationship. Additionally, participants reported employing collaborative approaches as the most frequent conflict management strategy. These results underscore the urgent need for organizations to implement targeted conflict management training programs and psychological and emotional support initiatives to alleviate the adverse effects of emotional labor on burnout. By fostering healthier workplace environments, organizations can enhance employee well-being and productivity.